1997
DOI: 10.1093/clinids/24.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epicardial Pacing Wire Cultures in the Diagnosis of Poststernotomy Mediastinitis

Abstract: Mediastinitis after cardiac surgery is difficult to diagnose in many cases. The transitory epicardial pacing wires used after surgery are placed in the mediastinum, so the culture of these wires could be useful for the diagnosis of this disease. To test this hypothesis, we routinely cultured the epicardial pacing wires of 565 patients undergoing extracorporeal circulation. Wires were removed on the 7th to 9th postoperative day under sterile conditions and were cultured with routine techniques used for the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
1
14
1
3
Order By: Relevance
“…Pacing wires are fixed in the pericardium at the end of cardiac surgery operations and can be considered microbiological samples of the anterior mediastinum. Three previous studies have evaluated the accuracy of EPW cultures in the early prediction of PSM (2,8,12), but these series comprised small numbers of patients with PSM, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacing wires are fixed in the pericardium at the end of cardiac surgery operations and can be considered microbiological samples of the anterior mediastinum. Three previous studies have evaluated the accuracy of EPW cultures in the early prediction of PSM (2,8,12), but these series comprised small numbers of patients with PSM, …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that EPW cultures might be helpful in the early diagnosis of PSM (2,8,12). However, these studies included only a small number of patients with PSM (35 patients in all).…”
mentioning
confidence: 99%
“…Because of this limitation, a variety of diagnostic approaches to the diagnosis of mediastinitis have been evaluated, including aspiration of the mediastinal space, 14,15 ␣ 1 acid glycoprotein and C-reactive protein measurements, 16 procalcitonin level, 17 and culture of perioperative instruments. 18 Even advanced, expensive methods of radiographic imaging such as computed tomography, 19,20 fluorine-18 fluorodeoxyglucose positron emission tomography, 21,22 gallium-67 scintigraphy, 23 99Tcm-labeled leukocyte scintigraphy, 24,25 or single photon emission computed tomography with 99mTc-hexamethylpropylene amine oxime-labeled leukocytes 26 are either of limited benefit in identifying patients with postoperative mediastinitis or are widely unavailable. For example, the sensitivity and positive predictive value of computed tomography in the diagnosis of mediastinitis were as low as 25% and 71%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial pacing wire cultures are not satisfactory for the diagnosis of mediastinitis [50] , while bacteriological samples from the sternal or retrosternal puncture are considered safe and powerful [51] . CT scans have been considered of great value to localize infected tissues [52] , however, there is also some doubt about the validity of a CT scan in performing an early diagnosis [53,54] .…”
Section: Diagnosismentioning
confidence: 99%